The relationship between top management communication performance and job satisfaction. - J. David Pincus; Robert Rayfield (Communicare)
THIS field study of 327 professional hospital nurses Investigates the relationship between employees' perceptions of top-level management organizational communication and employee job satisfaction and job performance. Pearson product-moment and canonical correlation analyses revealed significant positive relationships between top management communication and employee job satisfaction and, to a lesser ex tent, with job performance. Although considerable research has been conducted into the immediate supervisor employee communication relationship, which has demonstrated a strong, positive association, the top management-employee communication link has been largely overlooked. Findings here suggest that employees look to top managers and im mediate supervisors to fulfill separate and distinct communication needs. This study sought to pave the way for more research into the effects of top management communication on various orginizational effectiveness variables. The authors draw conclusions from their fin dings, propose a model for future research and suggest future research directions.